2020
DOI: 10.3390/nano10040632
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Hydrazine Reduction Method for the Preparation of Nickel Nanoparticles, Physicochemical Characterization and Catalytic Application in Suzuki-Miyaura Cross-Coupling Reaction

Abstract: In the experimental work leading to this contribution, the parameters of the ultrasound treatment (temperature, output power, emission periodicity) were varied to learn about the effects of the sonication on the crystallization of Ni nanoparticles during the hydrazine reduction technique. The solids were studied in detail by X-ray diffractometry, dynamic light scattering, thermogravimetry, specific surface area, pore size analysis, temperature-programmed CO2/NH3 desorption and scanning electron microscopy. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Based on the results of the present study on phytochemicals with potent antioxidant activities, the BBS extract was selected to use in the green synthesis of NiONPs. Previously, NiONPs have been synthesised by physicochemical and biological methods [ 20 ]. However, the biocompatibility and phytochemical potential of BBS-NiONPs indicate that utilising medicinal plants for green synthesis is a much better strategy to synthesise pure, safe, biocompatible and bioactive NiONPs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the present study on phytochemicals with potent antioxidant activities, the BBS extract was selected to use in the green synthesis of NiONPs. Previously, NiONPs have been synthesised by physicochemical and biological methods [ 20 ]. However, the biocompatibility and phytochemical potential of BBS-NiONPs indicate that utilising medicinal plants for green synthesis is a much better strategy to synthesise pure, safe, biocompatible and bioactive NiONPs.…”
Section: Discussionmentioning
confidence: 99%
“…Meshkani et al [23] prepared a series of nickel catalysts with different contents of supported mesoporous spherical SiO2 by sol-gel method, and the experimental results showed that the samples prepared with 55% nickel performed the best in the temperature and stability tests. Ádám et al [24] used ultrasound-assisted reduction method to prepare nickel nanoparticles and carried out physical and chemical characterization. The experimental results showed that the ultrasonic prepared nickel nanoparticles had good catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…As actual catalysts, nickel nanoparticles (Ni NPs) have well-known popularity in liquid phase redox coupling reactions in conventional solvents such as toluene, alcohols or DMSO. [17,19,22] In our previous work, the desired transformations were indeed feasible in the presence of nickel nanocatalysts. In contrast to the studies reported, a significant but yet unknown rearrangement in the crystal phase of the nickel NPs was observed in parallel with their notable deactivation.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, there was no significant oxidation (either complete or partial) on the metallic surfaces. As actual catalysts, nickel nanoparticles (Ni NPs) have well‐known popularity in liquid phase redox coupling reactions in conventional solvents such as toluene, alcohols or DMSO [17,19,22] . In our previous work, the desired transformations were indeed feasible in the presence of nickel nanocatalysts.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation